Learning Activity with Problem-Based Learning Using Student Worksheet Assisted by MathCityMap to Improve Students' Mathematical Literacy - Zalsabila Yanuarriska Putri (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The AKM results at SMP Negeri 6 Pati indicate low mathematical literacy among students, necessitating innovative learning approaches that connect mathematical concepts to real-world contexts through technology. This study aims to design Problem-Based Learning using student worksheets assisted by MathCityMap to enhance students' mathematical literacy. The method employed is Design Research, comprising three stages: preparation and design, teaching experiment, and retrospective analysis. The research sample consisted of seventh-grade students in class VII A at SMP Negeri 6 Pati. Data collection techniques included tests, interviews, observations, documentation, and literature reviews. Validation results indicated that the tools were highly valid, with average scores of 90% for the teaching module, 93.5% for the media, and 95% for the literacy questions. The average pre-test score of 51 increased to 86.7 on the post-test. The Paired Sample T-Test showed a significant difference, and the N-Gain test yielded a score of 0.73 (high category). It was concluded that the Problem-Based Learning teaching tool using student worksheets assisted by MathCityMap is valid, feasible, and capable of improving students' mathematical literacy.